Experiment on the Melting Process of Wax: Implementation of Science Lab to Observe the Change of Solid to Liquid State - Adinda Febrianti Santoso; Elpia Suryani; Nurul Hasanah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research was conducted by students to examine the melting process as a form of change in state from a solid to a liquid through a simple experiment. The purpose of this study was to observe and understand how a solid, in this case, wax, undergoes a change from a solid to a liquid due to heat exposure. The method used was a direct experiment by heating wax in three varying volumes: 5 ml, 10 ml, and 15 ml, on a metal spoon placed over a flame. The results showed that the larger the volume of wax, the longer it took to melt. The 5 ml wax melted in 5 minutes, while the 15 ml wax took up to 11 minutes. This finding indicates a relationship between the amount of substance and the melting time, which is closely related to the heat energy received. This research confirms that melting is a reversible form of physical change, without changing the chemical structure of the substance. Through the students' experimental implementation, this study also demonstrated the effectiveness of a direct approach in strengthening understanding of basic science concepts and practicing scientific skills such as systematic observation, analysis, and inference about natural phenomena.